Megakaryocytic cells synthesize and platelets secrete α5-laminins, and the endothelial laminin isoform laminin 10 (α5β1γ1) strongly promotes adhesion but not activation of platelets - Nigatu, Ayele; Sime, Wondossen; Gorfu, Gezahegn; Geberhiwot, Tarekegn; Andurén, Ingegerd; Ingerpuu, Sulev; Doi, Masayuki; Tryggvason, Karl; Hjemdahl, Paul; Patarroyo, Manuel (Thrombosis and Haemostasis, 2006)
Following vascular injury, basement membrane (BM) components of the blood vessels are exposed to circulating cells and may contribute to hemostasis and/or thrombosis. Laminins 8 (LN-8) (α4β1γ1) and 10 (LN-10) (α5β1γ1) are major laminin isoforms of the endothelial BM, and LN-8 is also secreted by activated platelets. In the present study, we demonstrate synthesis of α5-laminins LN-10 and LN-11 (α5β2γ1) by megakaryocytic cells, and intracellular expression of these laminin isoforms in blood platelets. In contrast to platelet LNα4 chain that had an apparent molecular weight of 180 kDa and associated mostly to LNβ1 chain, platelet LNα5 consisted of 300/350 kDa polypeptides and associated mainly to LNβ2. Both α4– and α5-laminins were secreted by platelets following stimulation. When compared to recombinant human (rh) LN-8, rhLN-10 was much more adhesive to platelets, though adhesion to both proteins was largely mediated via α6β1 integrin. In spite of their adhesive properties, rhLN-8 and rhLN-10 induced neither P-selectin expression nor cell aggregation, two signs of platelet activation. This study demonstrates synthesis/expression of heterotrimeric α5-laminins in hematopoietic/blood cells, and provides evidence for the adhesive, but not activating, role of endothelial laminin isoforms in platelet biology.
Keywords: Endothelial laminins; platelet adhesion/activation; integrins